Electron-hole Fermi liquid in nanosized semiconductor structures - Litovchenko, V.G.; Grygoriev, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The experimental and theoretical results on the quantum-sized electron-hole liquid plasma (EHLP) in semiconductors and analysis of the difference of it in comparison to the bulk one have been presented. The non-equilibrium Fermi EHLP can be created in the bulk and layered structures (insulator-semiconductor interfaces, thin films, quantum superlattices, etc.) at low temperatures and powerful laser radiation. In the quantum-sized structures, however, these phenomena appear at much higher temperatures, up to the room ones. The peculiarities of EHLP phenomena are: (1) appearance the very broad luminescence line in the low-energy side of its spectrum, which have constant width and energy position under variation of the light intensity as well as narrowing peak when increasing the temperature; (2) appearance of stimulated radiation with a relatively low excitation threshold (the so-called “surface laser effect”); (3) planar ballistic expansion of electron-hole plasma over long distances; (4) predicted effect of transformation of non-equilibrium 2D plasmons into radiative modes.